REVEALING THE ROLE OF FINANCIAL MANAGEMENT IN THE ANTECEDENT OF AUDIT QUALITY IN THE AUTOMOTIVE SECTOR IN INDONESIA - Indriani, Etty; Khristiana, Yenni; Putri, Ika Swasti; Angelina, Yosephine (International Journal of Accounting & Finance Review, 2024)
Audit quality, as an important element to maintain investor trust, is influenced by financial management factors such as financial ratios, intellectual capital, and dividend policy. However, empirical research examining the influence of these factors on audit quality in the Indonesian automotive sector is still limited. This study aims to analyze the relationship between financial ratios, intellectual capital, and dividend policy on audit quality in automotive companies listed on the Indonesia Stock Exchange during the period 2013–2021. Secondary data used include financial information, dividend policy, intellectual capital (measured by the number of employees, level of innovation, and research and development activities), and audit quality based on external auditor assessments. This study uses a quantitative approach with the logistic regression method to test the significant effect of the three variables on audit quality, considering control variables such as company size and operational complexity. The results show that financial ratios, intellectual capital, and dividend policy contribute significantly to audit quality. These findings provide significant implications for investors, capital market authorities, regulators, and company management. For investors, the results of this study can be used as a guide in assessing the audit quality of automotive companies, thus impacting their investment decisions. Meanwhile, for company management, these results are an encouragement to improve the quality of financial reporting. Thus, improvements in corporate governance and oversight mechanisms will contribute to the creation of a more transparent, accountable, integrity-based, and sustainable business environment, which not only improves the company's reputation but also supports the long-term growth of the Indonesian automotive industry in the global market.JEL Classification Codes: C12, G320, M42, N65.